2015
DOI: 10.1111/cpr.12171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurotrophin receptor‐mediated MAGE homology on proliferation and odontoblastic differentiation of mouse dental pulp cells

Abstract: NRAGE is a potent regulator of proliferation and odontoblastic differentiation of mDPCs, which might be via the NF-κB signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Our experiments consistently demonstrated that high GLU, particularly at the concentrations of 25 and 50 mM, markedly suppressed human DPC proliferation and promoted cell apoptosis. ALP is a marker of odontoblastic differentiation and its activity is enhanced during odontoblastic induction (33,34). We found that high GLU inhibited ALP activity and mineralization in DPCs, suggesting that high GLU inhibited the proliferation and differentiation and induced the apoptosis of DPCs.…”
Section: Discussionmentioning
confidence: 66%
“…Our experiments consistently demonstrated that high GLU, particularly at the concentrations of 25 and 50 mM, markedly suppressed human DPC proliferation and promoted cell apoptosis. ALP is a marker of odontoblastic differentiation and its activity is enhanced during odontoblastic induction (33,34). We found that high GLU inhibited ALP activity and mineralization in DPCs, suggesting that high GLU inhibited the proliferation and differentiation and induced the apoptosis of DPCs.…”
Section: Discussionmentioning
confidence: 66%
“…indicated that Mage‐D1‐deficient osteoclasts exhibited a higher expression of canonical NF‐kappaB and resulted in increased osteoclastogenesis but not osteoblastogenesis. Reports indicated that Mage‐D1 showed a negative effect on differential mineralization in differentiated cell lines similar to calvarial osteoblasts and dental pulp cells . Knockdown of Mage‐D1 significantly down‐regulated the potential of differential mineralization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicated that Mage-D1 showed a negative effect on differential mineralization in differentiated cell lines similar to calvarial osteoblasts 26 and dental pulp cells. 51 Knockdown of Mage-D1 significantly down-regulated the potential of differential mineralization (Fig. 7a,b,d) in EMSCs, suggesting that the "connection" of p75NTR and Mage-D1 with mineralizationrelated genes was attenuated (Fig.…”
Section: Mage-d1 and Ngf Play Important Roles Of Mineralized Differmentioning
confidence: 96%
See 1 more Smart Citation
“…Leukaemia inhibitory factor promotes the proliferation of DPCs, and inhibits the odontoblastic differentiation via the Jak2‐Stat3 signalling pathway. NRAGE regulates the odontoblastic differentiation of hDPCs through NF‐kB signalling pathway . The ERK signalling pathway plays important roles in odontogenic differentiation of hDPSCs and repair after dental pulp injury.…”
Section: Discussionmentioning
confidence: 99%